Flow of Newtonian Fluid in Non-Uniform Tubes with Application to Renal Flow: A Numerical Study (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, a numerical method employing a finite differencetechnique is used for an investigation ofviscous, incompressible fluid flow in a tube with absorbing walland slowly varying cross-section. The effectof fluid absorption through permeable wall is accounted byprescribing flux as a function of axial distance.The method is not restricted by the parameters in the problemsuch as wave number, permeability parameter,amplitude ratio and Reynolds number. The effects of these parameterson the radial velocity and mean pressuredrop are studied and the results are presented graphically. Comparisonis also made between the results obtained byperturbation method of solution and present approach.